PERAN BENDA ASLI (REAL OBJECT) DAN PEMANFAATANNYA DALAM PROSES PEMBELA.JARAN DI SEKOLAH DASAn - Sungkono Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Study in elementary school would be effective if instructionalmaterial discussion takes place concretely, remembers thecognitive development of elementary school student stays atconcrete level. Presentation of instructional material will haveconcrete characteristic when the study using or exploits realobject. Real object can be classified in two that is object andspecimen.Real object has vital importance role in study activity atelementary school. The role seems lo starling ji-om pre-studyactivity that is stimulating and motivates student in followinglesson; al study core activity, original object ha.i role that isassisting to watch over attention and grows active activity; and therole of utilization real object al follow-up study activity, studentwould more free lo do enrichment material which has been studiedUtilization of real object in study ac:ivily can be through in twotechniques that are bringing class to external world and bringsworld into class. So the utilization can run effective, ejpeciallyteacher need to go through phases and utilization stages oft he realobject.